Nomogram of Effective Length Coefficient of Frame Column. Issue 6 (March 2019) - Wu, Shilong; Zhou, Donghua; Li, Lu
Abstract: In this paper, the method of making a nomogram of the length calculation coefficient of the frame column is elaborated. There are two types of frame columns: no sideways and sideways. Therefore, there are two types of corresponding calculation lengths. In the common literature, the calculated length factor μ is made into a table. However, it is difficult to list all the situations, and making a nomogram can overcome this shortcoming. A nomogram can represent all the changes of μ with the constraint stiffness and the usage is simple and convenient. It only needs to select the point to connect the straight line, and the obtained μ value precision also meets the requirements of actual engineering calculation.